Development of Quantitative Structure Property relationships to Estimate Occupational Exposure Limit Values - Phung , Thi Kieu Trang (Universiti Teknologi Petronas, 2011)
Occupational Exposure Limits (OELs) are representing the amount of a workplace health hazard that most workers can be exposed to without harming their health. There are different OELs such as threshold limit value (TLV of ACGIH), permissible exposure limit (PEL of OSHA), recommended exposure limit (REL of NIOSH) and maximum concentration value in the workplace (MAK of DFG) can be found from different literatures and databases. Perhaps, the database provided by Yaws, (2003) can present various values for organic and inorganic chemicals. However, there are several compounds do not have these values. The traditional way to measure these values are using experimental methods. This is can be costly and time consuming. Therefore, this project intent to develop quantitative structure property relationships to estimate occupational exposure limits values. A new method for the estimation of properties of pure organic compounds is presented. Estimation is performed at three levels. The primary level uses contributions from simple groups that allow describing a wide variety of organic compounds while the higher levels involves poly functional and structural groups that provide more information about molecular fragments whose description through first-order groups is not possible.